Consolidating lung volume reduction surgery after endoscopic lung volume reduction failure - Eichhorn, Martin E.; Gompelmann, Daniela; Hoffmann, Hans; Dreher, Sascha; Hornemann, Katrin Emma; Haag, Johannes C.; Kontogianni, Konstantina; Heußel, Claus Peter; Winter, Hauke; Herth, Felix; Eberhardt, Ralf (The annals of thoracic surgery, 2021)
Background - Bronchoscopic valve placement constitutes an effective endoscopic lung volume reduction (ELVR) therapy in patients with severe emphysema and low collateral ventilation. After the most destroyed lobe is occluded with valves, significant target lobe volume reduction leads to improvements in lung function, exercise capacity, and quality of life. The effects are not consistent in some patients, leading to long-term therapy failure. We hypothesized that surgical lung volume reduction (LVRS) would reestablish ELVR short-term clinical improvements after ELVR long-term failure. - Methods - This retrospective single-center analysis included all patients who underwent consolidating LVRS by lobectomy after long-term failure of valve therapy between 2010 and 2015. Changes in forced expiratory volume in 1 second, residual volume, 6-minute walking distance, and Modified Medical Research Council dyspnea score 90 days after ELVR and LVRS were analyzed, and the outcomes of both procedures were compared. - Results - LVRS was performed in 20 patients after ELVR failure. A lower lobectomy was performed in 90%. The 30-day mortality of the cohort was 0% and 90-day mortality was 5% (1 of 20). The remaining 19 patients showed a significant increase in forced expiratory volume in 1 second (+27.5% ± 19.4%) and a reduction in residual volume (−21.0% ± 17.4%) and total lung capacity (−11.1% ± 11.1%). This resulted in significant improvements in exercise tolerance (6-minute walking distance: +56 ± 60 m) and relief of dyspnea (ΔModified Medical Research Council: −1.8 ± 1.4 points.). - Conclusions - Consolidating LVRS by lobectomy after failure of a previously successful ELVR is feasible and results in significant symptom relief and improvement of lung function.
Gesehen am 05.08.2021
First published: 28 September 2020